PENGARUH INFLASI, NILAI TUKAR, PRODUK DOMESTIK BRUTO, DAN PERTUMBUHAN PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN INDUSTRI KIMIA, FARMASI, DAN OBAT TRADISIONAL PERIODE 2016 – 2021 - Permatasari, Alisyah; Sulistyowati, Sulistyowati (Journal of Accounting, Management and Islamic Economics, 2024)
The result of stock investing is the stock return. Stocks are one of the financial vehicles that investors are interested in due to its propensity to produce significant returns while also posing hazards. Investors must make reasonable decisions before investing by acquiring knowledge from both the internal (microeconomic) and exterior (macroeconomic) domains. Thus, the purpose of this research is to investigate the macroeconomic effects represented by inflation, exchange rates, and GDP, as well as the microeconomics represented by corporate growth. The sample used a purposive sampling technique and included 26 enterprises, including 6 pharmaceutical and traditional medicine companies and 20 chemical companies. using a 6-year study period. Panel data regression was employed as the analytical tool in this study, which was processed using Eviews 12. The results revealed that the inflation variable had a considerable negative effect on stock returns, whereas the exchange rate, GDP, and company growth factors had no effect. At the same time, the variables Inflation, Exchange Rate, GDP, and Company Growth all have an impact on stock returns. The study's findings have consequences for the government, businesses, and investors seeking to ensure the independence of the domestic health ecosystem.Keywords: Input Innovation, Process Innovation, Product Innovation, Organizational Innovation, Productivity and Company Performance.